The Influence Of Competence And Teamwork on Employee’s Performance of Agriculture, Crops and Horticulture Service, South Sumatera Province - Agustina Hanafi (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Agriculture, Crops and Horticulture Service, South Sumatera Province has a big responsibility to reach crop production target. It is very much influenced by the performance of employees. The purpose of this study was to analyze the influence of competence and teamwork on the performance of the civil servants of Agriculture, Crops and Horticulture Service, South Sumatera Province. The sample of this study were 101 civil servants from some different divisions those are Secretary, Crop Production, Infrastructure for Agricultural Production and Management and Agricultural Trade. The data were obtained through questionnaire, analyzed by using multiple regression test at α = 0,05. Explanatory approach was done to analyze the Influence of Competence and Teamwork on the civil servants of Agriculture, Crops and Horticulture Service, South Sumatera Province. The result of this study showed that partially, competence had no significant influence meanwhile teamwork had. Simultaneously, competence and teamwork had positive and significant influence on the civil servants performance. Teamwork has more dominant influence compared to the competence on the employee performance